2016
DOI: 10.1074/jbc.m116.751420
|View full text |Cite|
|
Sign up to set email alerts
|

O-GlcNAcase Is an RNA Polymerase II Elongation Factor Coupled to Pausing Factors SPT5 and TIF1β

Abstract: We describe here the identification and functional characterization of the enzyme O-GlcNAcase (OGA) as an RNA polymerase II elongation factor. Using in vitro transcription elongation assays, we show that OGA activity is required for elongation in a crude nuclear extract system, whereas in a purified system devoid of OGA the addition of rOGA inhibited elongation. Furthermore, OGA is physically associated with the known RNA polymerase II (pol II) pausing/elongation factors SPT5 and TRIM28-KAP1-TIF1␤, and a purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 74 publications
6
21
0
Order By: Relevance
“…Previous experiments showed that inhibition of OGA in the CFS blocked elongation 14 , as effectively as the CDK9 and PARP-1 inhibitors in this study. Those experiments indicated that OGA catalytic activity was required for elongation and secondly, that OGT must have acted prior to that point in order to create a substrate for the OGA.…”
Section: O-glcnac Cycling Is Necessary For Rna Pol II Pausing and Elosupporting
confidence: 70%
See 2 more Smart Citations
“…Previous experiments showed that inhibition of OGA in the CFS blocked elongation 14 , as effectively as the CDK9 and PARP-1 inhibitors in this study. Those experiments indicated that OGA catalytic activity was required for elongation and secondly, that OGT must have acted prior to that point in order to create a substrate for the OGA.…”
Section: O-glcnac Cycling Is Necessary For Rna Pol II Pausing and Elosupporting
confidence: 70%
“…This is easily done by conjugating biotinylated-CMV promoter template to magnetic beads. Using this assay system, one can isolate various steps in the transcription processes wash off soluble factors, and then add back the activity in question to assess its function 14,30,31 . As indicated in Figure 3A, a 30" pulse was used to label RNA and transcription was stopped with EDTA.…”
Section: P-tefb and Super Elongation Complex Stimulate Pause Release mentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of transcription factors and co-activator/co-repressor complexes by O-GlcNAc is poorly understood. OGT is part of the mSin3A complex (Yang et al 2002) and the polycomb complex (Chu et al 2014;Maury et al 2015); and both OGA and OGT help organize the RNA Pol II pre-initiation complex (Ranuncolo et al 2012;Lewis et al 2016;Resto et al 2016). Recent advances in O-GlcNAc crosslinking technology will aid in the determination of which proteins interact with O-GlcNAcylated transcriptional complexes, how these complexes change in response to different stimuli, and potentially identify protein domains that preferentially bind to O-GlcNAcylated moieties (Rodriguez et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…OGT also interacts with mSin3A or components of the polycomb repressive complex (PRC) 1 and 2 to mediate transcription repression by forming stable repressor complexes (Yang et al 2002;Chu et al 2014;Maury et al 2015). OGT and OGA regulate preinitiation complex (PIC) formation and RNA Polymerase II (Pol II) activity (Ranuncolo et al 2012;Lewis et al 2016;Resto et al 2016).…”
Section: Introductionmentioning
confidence: 99%